Actoprotective activity of some 5-(thiophen-3-ylmethyl)-4-R1-1,2,4-triazole-3-thiols derivatives - O. A. Bihdan (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Today, the process of body fatigue has many definitions, but in general it is characterized as a feeling of heaviness arising from the initiation or support of voluntary physical or mental activity associated with working at the level of one's normal abilities. Fatigue of the body, as a physiological norm, can be divided into physical fatigue and mental fatigue. The solution to the problem of therapy for the process of fatigue should be expressed in the creation of new effective compounds that can affect the mechanisms of fatigue development and can be oriented towards restoration of cell function, as well as increase the activity of enzymes of the antioxidant defense system of the body in a certain way. The aim of our work was to investigate the actoprotective activity of new derivatives of 5-(thiophen-3-ylmethyl)-4-R1-1,2,4-triazole-3-thiol and to establish certain patterns between the chemical structure and pharmacological activity of the studied compounds. The studies used new derivatives of 5-(thiophen-3-ylmethyl)-4-R1-1,2,4-triazole-3-thiol, which were first synthesized in the laboratory of organic synthesis of the Department of Natural Sciences for foreign students and toxicological chemistry of Zaporizhzhia State Medical University. o determine the dosage conditions of the studied compounds, a preliminary study was made of the general toxic effect and acute toxicity of the studied compounds, which was carried out according to the well-known express method of V. B. Prozorovsky, and the degree of toxicity was evaluated by K. K. Sidorov. The experiments were performed on a group of white nonlinear rats weighing 230-245 g. In the study of actoprotective activity was used the method of forced immersion in water with a load of 10% of the weight of the rat. The data obtained were processed statistically using the standard Microsoft Office 2007 software package and "STATISTICA @ for Windows 6.0". The reliability of intergroup differences according to the experimental data was established using Student's t-test. The level of statistical significance of differences in research results is p < 0.01. Analyzing the results of the experiment, it was found that some compounds that were studied in a number of new derivatives of 5-(thiophen-3-ylmethyl)-4-R1-1,2,4-triazole-3-thiol have a pronounced actoprotective effect. The actoprotective activity of the new derivatives of 5-(thiophen-3-ylmethyl)-4-R1-1,2,4-triazol-3-thiol was studied. A number of compounds have been identified that are superior in activity to the comparison drug riboxin. In some cases, patterns of the influence of various substituents on the indices of the actoprotective action of the synthesized compounds were established.